Coding projects in Scratch - Woodcock, Jon (DK Publishing, 2016)
You can learn to create mind-bending illusions, crazy animations, and interactive artworks with this collection of Scratch projects! Woodcock shows you simple steps to becoming an expert coder, and helps you improve your coding skills so you can share games online.